'Killing them softly with this song ...' The literary structure of Psalm 3 and its Psalmic and Davidic Contexts. Part I : an intratextual interpretation of Psalm 3 - Botha, Phil J. (Old Testament essays, 2008)
This is the first article in a series of two which investigate the meaning of Psalm 3. In this contribution, the syntax of the verbs and the aspects of time in Psalm 3 are analysed. This is correlated with a poetic analysis of the psalm. A division of three stanzas (2-4 5- 7 8-9) is proposed in which each of the three sections is seen to describe a movement from prayer to a confession of trust. The first and the last stanza seem to be two parts of a prayer in the present tense, spoken by a suppliant who is under attack from a large number of enemies. The central stanza seems to contain a description of a prayer by the same person in the past, as well as the nocturnal answer of YHWH to this prayer, something that gave the suppliant the courage in his present situation of distress to react with confidence to the fear instilled by the enemies and their words.